Synthesis of Chitosan Composite based on Black Soldier Fly (BSF) Exuviae with Kipahit Leaf Extract and its Inhibition Test against Xanthomonas Oryzae. - Wahyuni, Sri; Fauziyah, Ridha; Aziz, Muhammad Abdul; Eris, Deden Dewantara; Prakoso, Haryo Tejo; siswanto, Siswanto; Priyono, Priyono (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2021)
HDB disease caused by the bacteria Xanthomonas oryzae pv.oryzae (Xoo) is an important disease in rice plants. Recently, many organic based antibacterial agents are being developed, one of which is chitosan. One of the potential raw materials for producing chitosan is Black Soldier Fly (BSF) exuviae. During the development, chitosan was formulated with other ingredients such as kipahit leaves (Tithonia diversifolia). The purpose of this study is to synthesize BSF-based chitosan, formulate BSF-based chitosan composites with kipahit leaf extract using 0.1% sodium tripolyphosphate and test the antibacterial activity against Xanthomonas oryzae composites. The process of optimizing the extraction of kipahit leaves was carried out with a variety of solvents (2% acetic acid, 96% ethanol and 20% DMSO). The antibacterial activity test was carried out by the disc diffusion method at a concentration of 0.1; 0.2; 0.4; 0.6; 0.8 and 1% (w / v). The results showed that the best kipahit leaf extraction was obtained using 96% ethanol as a solvent.Â